Answer:
Convert into same base
Step-by-step explanation:
Convert both sides into same bases and equate the powers to solve for the variable.
Example:
8^x = 32
You can either use logs to bring the power down or convert both sides into the same base
8 = 2³
8^x = (2³)^x = 2^(3x)
32 = 2⁵
2^(3x) = 2⁵
3x = 5
x = 5/3
x = 1⅔
Answer:
-2
Step-by-step explanation:
First, you need to find the equation.
f(x) = -3x + b
Now we need to find the y-intercept.
f(x) = -3x + b
f(-9) = -3(1) + b
-9 = -3 + b
-6 = b
f(x) = -3x - 6
The zero of f means that f(x) = 0
f(0) = -3x - 6
f(6) = -3x
x = -2
10% of 14 =1.4
14-1.4=12.6
6% of 14=0.84
12.6+0.84= 13.45
The variation of K is what is found in front of X